Cerebrospinal fluid pressure in glaucoma: a prospective study - Ren, Ruojin; Jonas, Jost B.; Tian, Guoghong; Zhen, Yi; Ma, Ke; Li, Shuning; Wang, Hongtao; Li, Bin; Zhang, Xiaojun; Wang, Ningli (Ophthalmology, 2010)
Purpose - To assess whether a low cerebrospinal fluid pressure (CSF-P) is associated with open-angle glaucoma in eyes with normal intraocular pressure (IOP). - Design - Prospective, interventional study. - Participants - The study included 43 patients with open-angle glaucoma (14 with a normal IOP, and 29 with an elevated IOP) and 71 subjects without glaucoma. - Interventions - All patients underwent standardized ophthalmologic and neurologic examinations and measurement of lumbar CSF-P. - Main Outcome Measures - Cerebrospinal fluid pressure and IOP. - Results - Lumbar CSF-P was significantly (P<0.001) lower in the normal IOP glaucoma group (9.5±2.2 mmHg) than in the high IOP glaucoma group (11.7±2.7 mmHg) or the control group (12.9±1.9 mmHg). The trans-lamina cribrosa pressure difference (IOP minus CSF-P) was significantly (P<0.001) higher in the normal IOP glaucoma group (6.6±3.6 mmHg) and the high-IOP glaucoma group (12.5±4.1 mmHg) than in the control group (1.4±1.7 mmHg). The extent of glaucomatous visual field loss was negatively correlated with the height of the CSF-P and positively correlated with the trans-lamina cribrosa pressure difference. In the control group, CSF-P was significantly correlated with both systolic blood pressure (P = 0.04) and IOP (P<0.001). The trans-lamina cribrosa pressure difference was not significantly associated with blood pressure (P = 0.97). - Conclusions - In open-angle glaucoma with normal IOP, CSF-P is abnormally low, leading to an abnormally high trans-lamina cribrosa pressure difference. Pathogenetically, a low CSF-P in normal-IOP glaucoma may be similar to a high IOP in high-IOP glaucoma. Consequently, the glaucomatous visual field defect is positively correlated with the trans-lamina cribrosa pressure difference and inversely correlated with the CSF-P. In nonglaucomatous subjects, CSF-P, blood pressure, and IOP are significantly associated with each other. - Financial Disclosure(s) - The authors have no proprietary or commercial interest in any of the materials discussed in this article.
Online verfügbar 6. Dezember 2009
Gesehen am 12.05.2023